Pengelolaan Daya Tarik Wisata Budaya Pura Puseh Pura Desa, Desa Pekraman Batuan, Gianyar - Suryaningsih, Ni Wayan Eka; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2018)
“Pura Puseh Pura Desa” keeps safely the inheritance things and its histories in the past. In addition, the existence of unique spiritual rituals of Batuan people as cultural attraction will support the development of “Pura Puseh Pura Desa”  become a cultural tourism which is managed by elitist of Batuan village. This research is located in Batuan village, Gianyar regency. The type of data in this research is qualitative data. The data source obtained from primary and secondary data . The method of this research is descriptive qualitative data that collected through through interview s, observation, and documentation . The determination of informant used purposive sampling. The result of this research shows that “Pura Puseh Pura Desa” become an attracttion of cultural tourism which is managed by elite as the representative of Batuan village. The managed “Pura Puseh Pura Desa” by doing function of management such as planning, organization, actuating, controlling.   Keyword: Management of tourist attraction, elite , Pura Puseh Pura Desa, cultural tourism